Хараа, Орхон, Сэлэнгэ голуудын хөндийд тархсан суумтгай хөрсний геотехникийн нөхцөлийн зураглалд - Б., Бат; З., Ганбаатар; Э., Болормаа; Б., Хосбаяр (Geological Issues, 2022)
In the framework of research engineering geological conditions and mapping of loess type soil in Orkhon-Kharaa-Selenge basins: Summarizing and analyzing previous research works, Field research such as a sampling-testing-mapping with portable small tools, Qualitative quantification of laboratory parameters of the physical and mechanical properties of soil in monolithic samples, Determination of soil mineralogical composition by high-level laboratory experiments, Comparison and use of quantitative data from laboratory experiments and field tests, Loess-type soil distribution mapping, and Stationary data processing were performed. This research was conducted by a team of researchers from the Department of Geology and Geophysics of the National University of Mongolia, as part of a high level research project starting in 2017 in Darkhan uul, Orkhon and Selenge aimags.